The level of availability of scientific research skills as imagined by postgraduate students - Ahmed Mohamed Hamad Al-Burky (Social Empowerment Journal, 2023)
This study aimed to recognize the level of availability of scientific research skills as imagined by postgraduate students in some colleges at Benghazi University. It also aimed to recognize whether there are statistically significant differences in the level of availability of scientific research skills (implementation of scientific research steps, writing scientific research, interpretation and analysis of scientific research results, search skills in databases, information sources, and electronic libraries on the Internet), which are attributed to some of their demographic and academic variables (gender, scientific sabbatical to study, college, and scientific department). Its results revealed that the scientific research skills, as imagined by postgraduate students were available at an average level in the researched faculties, with an arithmetic mean of 3.304. The results also revealed no statistically significant differences in the levels of availability of scientific research skills, which are attributed to some of their demographic and academic variables. The study recommended providing annual subscriptions to digital libraries for postgraduate students.